2003
DOI: 10.1053/jlts.2003.50079
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus as primary immunosuppression in liver transplantation is not associated with hepatic artery or wound complications

Abstract: Sirolimus is a new immunosuppressive agent increasingly being used in liver transplant recipients. There is concern that sirolimus may be associated with wound complications and hepatic artery thrombosis (HAT). We have used sirolimus as primary immunosuppression in 170 liver transplant recipients and therefore reviewed our experience with wound complications and HAT in our cohort of patients. Records of all 170 patients administered sirolimus as primary immunosuppression and 180 historic controls were reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
2
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(55 citation statements)
references
References 25 publications
5
45
2
3
Order By: Relevance
“…The average proliferation index was dramatically decreased from 62.8 ± 12.7% in rapamycin treatment group to 29.8 ± 6.5% in the group that received both rapamycin and bortezomib. Rapamycin has showed antiangiogenic activities in vivo not only by decreasing the production of VEGF but also by inhibiting the response of vascular endothelial cells on stimulation by VEGF via inhibiting of mTOR [41]. One mechanism of bortezomib-induced tumor growth inhibition identified in previous studies is also angiogenesis inhibition [42].…”
Section: Discussionmentioning
confidence: 99%
“…The average proliferation index was dramatically decreased from 62.8 ± 12.7% in rapamycin treatment group to 29.8 ± 6.5% in the group that received both rapamycin and bortezomib. Rapamycin has showed antiangiogenic activities in vivo not only by decreasing the production of VEGF but also by inhibiting the response of vascular endothelial cells on stimulation by VEGF via inhibiting of mTOR [41]. One mechanism of bortezomib-induced tumor growth inhibition identified in previous studies is also angiogenesis inhibition [42].…”
Section: Discussionmentioning
confidence: 99%
“…Two multicenter randomized studies in de novo liver transplant recipients suggested that the use of sirolimus in combination with cyclosporine or tacrolimus was associated with an increase in HAT [38, 44]. In subsequent studies (a mixture of quality and trial designs) that reviewed the use of sirolimus in liver transplant recipients, increased rates of HAT have not been observed (Table 4(a)) [15, 45, 48, 53, 55, 57, 61]. In fact, two of these studies recorded significantly lower incidences of HAT among patients receiving sirolimus compared to controls [53, 57].…”
Section: Resultsmentioning
confidence: 99%
“…In seven studies, wound complications (described as either wound complications, wound dehiscence, wound infection, healing complications, or slow wound healing) were reported in 2.2–15% of liver transplant recipients receiving sirolimus (Table 4(b)) [15, 48, 53, 55, 61, 69, 78]. Six of these studies included a control group, of which five (a mixture of quality and trial designs) demonstrated no significant difference in wound complications between sirolimus and control groups [15, 53, 55, 61, 69, 78] and one small study demonstrated a significantly lower incidence of poor wound healing versus the CNI group ( P = 0.017) [48]. Two of the studies reported that the incidence of incisional hernia was also similar in liver transplant recipients receiving sirolimus or CNIs [48, 53].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this drug has also been used off-label in liver and lung transplantation patients [24][25][26][27] . At our center, the use of everolimus in LT recipients is approved in situations such as renal dysfunction or adverse events like neurotoxicity due to CNI, development of de novo malignancies, recurrence of hepatocellular carcinoma, and the presence of predictors of a high risk of hepatocellular carcinoma recurrence in the explanted liver (satellitosis, vascular infiltration and multinodularity disease) [28,29] . Con- traindications for the use of everolimus are a prior history of hepatic artery thrombosis, proteinuria greater than 800 mg/d and/or surgery in the previous 4 wk [29,30] .…”
Section: Methodsmentioning
confidence: 99%